(untitled) (Journal of Atomic and Molecular Sciences, 2015)
The additivity rule for electron scattering from molecule has been revised by considering the difference between the free atom and the corresponding bound atom in the molecule. The total cross sections for electron scattering from plasma etching molecules CF_4, C_2F_4, C_2F_6 and C_3F_8 have been calculated in the energy range from 100 eV to 5000 eV with the revised additivity rule. The present calculations are compared with the original additivity rule results and the existing experimental data. A better agreement between the present results and the experimental data is obtained.